Nocardia seriolae mediates liver granulomatous chronic inflammation in Micropterus salmoides through pyroptosis - Zhou, Zheng‐Yang; Bai, Shang‐Jie; Lu, Chen‐Wang; Yang, Bin; Wang, Jun; Lian, Sheng; Jian, Zheng‐Ran; Wang, Er‐Long; Wang, Gao‐Xue; Liu, Tao (Journal of fish diseases, 2023)
Granulomatous diseases caused by Nocardia seriously endanger the health of cultured fish. These bacteria are widely distributed, but prevention and treatment methods are very limited. Chronic granulomatous inflammation is an important pathological feature of Nocardia infection. However, the molecular mechanisms of granuloma formation and chronic inflammation are still unclear. Constructing a granuloma infection model of Nocardia is the key to exploring the pathogenesis of the disease. In this study, we established a granuloma model in the liver of largemouth bass (Micropterus salmoides) and assessed the infection process of Nocardia seriolae at different concentrations by analysing relevant pathological features. By measuring the expression of pro‐inflammatory cytokines, transcription factors and a pyroptosis‐related protein, we revealed the close relationship between pyroptosis and chronic inflammation of granulomas. We further analysed the immunofluorescence results and the expression of pyroptosis‐related protein of macrophage infected by N. seriolae and found that N. seriolae infection induced macrophage pyroptosis in vitro. These results were proved by flow cytometry analysis of infection experiment in vivo. Our results indicated that the pyroptosis effect may be the key to inducing chronic inflammation in the fish liver and further mediating granuloma formation. In this study, we explored the molecular mechanism underlying chronic inflammation of granulomas and developed research ideas for understanding the occurrence and development of granulomatous diseases in fish.